The Status of Tenualosa toli (Valenciennes, 1847) in the South- west Coast of Sarawak, Malaysia - Khairul, Adha; Shabdin, Mohd Long; Yuzine, Esa; A, Rahim; Mohamad Hambali, Tumiran; Ahmad, Awang (Graduate School of Kuroshio Science, 2014)
The tropical shad of genus Tenualosa (family Clupidae) or locally known as Terubok, are impor-tant estuarine fishes, both commercially and culturally in many Asian countries including Malaysia. However, Tenualosa species are subject to heavy fishing pressure and have suffered major declines. The decline of Tenualosa toli catch landing since 1980's had urged the state government of Sarawak to view with serious concern regarding the problem and directed research and development project to be conducted for maintaining and replenish the natural stock of the species in Sarawak. Therefore, this study was designated to examine the current status on the population of Tenualosa toli within Batang Lupar, Batang Lassa and Batang Saribas in the south-west coast of Sarawak which is known as "core Terubok areas". The informations that generated from this research will be useful for further studies not only on the ecology, distribution of Tenualosa but also on the conservation and sustainable man-agement of this commercial fish.